Validation of the Rosenberg Self-Esteem Scale among the Iranian adult population: A cross-sectional study - Saeed Ghasempour; Hamid Sharif-Nia; Soheil Nouri; Seyedmohammad Mirhosseini; Ali Abbasi (PLoS ONE, 2025)
Background Self-esteem refers to an individual’s overall sense of self-worth, which plays a crucial role in their well-being. One of the most commonly used instruments to measure this concept is the Rosenberg Self-Esteem Scale (RSES), which has been translated and psychometrically validated in numerous cultures and languages to date. Therefore, this study aimed to assess the psychometric properties of the Persian version of the RSES in the Iranian adult population. Methods This cross-sectional validation study was conducted following the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines in Shahroud city, northeastern Iran. A total of 533 adults from this city who spoke Persian and were literate were included in the study using convenience sampling. After translating and culturally adapting the RSES in accordance with World Health Organization (WHO) guidelines, face and content validity were assessed using both qualitative and quantitative methods. Additionally, construct validity was evaluated through exploratory and confirmatory factor analysis. Reliability was also determined by calculating Cronbach’s alpha coefficient, McDonald’s omega coefficient, composite reliability (CR), and intraclass correlation coefficient (ICC). Results The face and content validity of all items were confirmed through both qualitative and quantitative methods. Based on the results of the exploratory factor analysis using polychoric correlations and robust weighted least squares (WLSMV) estimation, the Persian version of this scale consists of two factors: (1) Positive self-esteem and (2) Negative self-esteem, which account for 59.1% of the total variance of the scale. All goodness-of-fit indices in the confirmatory factor analysis also supported this model (CMIN/ df = 2.29, RMSEA = .049, CFI = .981). These two factors showed acceptable internal consistency and stability, as evidenced by Cronbach’s alpha coefficients (.828 and .801), McDonald’s omega coefficients (.833 and .810), composite reliabilities (.820 and .796), and intraclass correlation coefficients (.838 and .875). Conclusion The findings of the current study showed favorable psychometric properties of the Persian version of the RSES for measuring self-esteem in the Iranian adult population.